Pluralitas Dalam Bingkai Hukum Islam - Aswarm Aswarm; Taskiah Latifm; Mustafan Arifm; Muhammad Amri (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The purpose of writing this work is to understand the concept of plurality within the framework of Islamic law. This research uses a literature review method to explore plurality in Islamic law. Data sources include the Al-Qur'an, hadith, and the Medina Charter, with data collection techniques using documentation and interview approaches. Data analysis was carried out descriptively and comparatively, and involved contextual studies to understand historical and social influences on Islamic legal views on plurality. The result of this work is that plurality in Islam, recognized as part of God's design and reflected in the Medina Charter, emphasizes tolerance and recognition of religious freedom. Within the framework of Islamic law in Indonesia, Islam plays a key role in managing plurality with the principles of justice and equality. Even though it is recognized in the 1945 Constitution and is in accordance with Pancasila, the challenges of implementing religious freedom still need to be overcome to create a harmonious society. It is hoped that a deep understanding of the concept of plurality can form an inclusive and fair legal framework in facing the complexities of contemporary times.